Performance analysis of a hybrid ground source heat pump system integrated with liquid dry cooler. (August 2019) - Hou, Gaoyang; Taherian, Hessam
Highlights: Introducing Dry Liquid Coolers to ground-source heat pump systems. Introducing a new Type in Trnsys to determine the direction of working fluid based on the value of watch temperature. Showing the effect of watch temperature on utilization of Dry Liquid Cooler. Abstract: Soil temperatures of a few meters underground range from 7 °C to 21 °C, and are relatively stable throughout the year, at least in milder climates. In order to take advantage of this relatively steady source of thermal energy underground for utilization in heating, ventilating and air-conditioning (HVAC) systems, a hybrid ground source heat pump (HGSHP) system is designed and assembled in Transient System Simulation tool (TRNSYS). Ground source heat pump (GSHP) system provides buildings with more efficient heating and cooling comfort at a higher coefficient of performance (COP) comparing to conventional HVAC units such as furnace, electrical resistance or air source heat pump. In order to improve the overall performance, various auxiliary components can be coupled to the original system to assemble a hybrid system. In this design, the system is presented as a horizontal ground loop in parallel with a liquid dry cooler. The flow of the working fluid of the hybrid system is controlled by a newly-developed type in TRNSYS, which serves as a functional part to improve the overall performance of the hybrid system. Both heating and cooling effects have been studied for a case study house located in Birmingham, Alabama. The model has also been tested in the climate of other cities. The simulations run for a full calendar year (simulation time) to generate important analytical data such as annual energy consumption and heat rate. After analyzing the results of various pipe lengths and diverter set-point temperatures, the optimal values have been recommended.